Modified pectic polysaccharide from turmeric (Curcuma longa): A potent dietary component against gastric ulcer. (15th March 2016) - Harsha, Mysore R.; Chandra Prakash, Serkad V.; Dharmesh, Shylaja M.
Highlights: Pectic polysaccharides were isolated from turmeric (TrPP) and modified (MTrPP). MTrPP displayed significantly higher levels of gastro-protection compared to TrPP. Comparative analysis indicated TrPP and MTrPP had different structural features. MTrPP had enriched homogalacturonan and galactan containing rhamnogalacturonan-I. Abundant galactans in MTrPP might target galectin-3 and exert antiulcer effect. Abstract: Native, intact (TrPP) and modified, low-molecular-weight (MTrPP) forms of pectic polysaccharides isolated from turmeric were evaluated for ulcer-preventive potentials in in vitro and in vivo models. Data indicated that MTrPP possessed significantly better ulcer-preventive property than TrPP; inhibiting ulcer scores up to 85%. Results were substantiated by effective muco-protection, H +, K + -ATPase down-regulation, inhibition of H. pylori growth/adherence, higher antioxidant/cytoprotective mechanisms. Structural data indicated TrPP and MTrPP differ in their molecular weights and structural characteristics with different sugar compositions and side chain ratios. MTrPP was rich in galacturonic acid (687 mg/g; TrPP—544 mg/g) and galactose (52.9%; TrPP—21.7%). Results were substantiated by NMR/FTIR data indicating the presence of homogalacturonan and rhamnogalacturonam-I containing galactans. By virtue of binding to inflammatory marker (galectin-3), galactans may reduce inflammation induced ulcerations. The low molecular weight of MTrPP (155 kDa; TrPP—13 kDa) may increase its bioavailability than TrPP, thus MTrPP may possess higher antiulcer potential.